The impact of a water promotion and access intervention on elementary school students in the presence of food insecurity - Leslie Gerstenfeld; Lauren Blacker; Charles E McCulloch; Lorrene D Ritchie; Valeria M Ordonez; Laura Schmidt; Anisha I Patel (Public Health Nutrition)
Abstract